The inhibiting factors of green product purchasing behavior: green knowledge as a moderating effect - Silintowe, Yunita Budi Rahayu; Sukresna, I Made (Business: Theory and Practice, 2023)
This study aims to analyze the effects of inhibiting factors (i.e., habits, skepticism, and lack of availability) and green knowledge on the purchasing behavior of environmentally friendly products. This research also explains the moderating effect of green knowledge on the relationship between the inhibiting factors of green product purchasing behavior and green product purchasing behavior. Prior studies have not investigated the moderating effect of green knowledge on the relationships between the inhibiting factors and green product purchases. Data was generated through a cross-sectional survey of 743 residents throughout Indonesia and analyzed by Partial Least Squares (PLS) as a variance-based technique for Structural Equation Modeling (SEM). The results demonstrate that green knowledge is crucial in affecting eco-friendly product purchasing decisions and consumers’ habits inhibit their decisions to purchase eco-friendly products. However, when moderated by better green knowledge, consumers who are not accustomed to purchasing eco-friendly products are more likely to make actual green product purchases. Further, the lack of green product availability demotivates consumers with higher green knowledge to purchase green products. This study offers practical implications for business actors by highlighting the importance of educating consumers on the positive environmental impacts of consuming green products and providing environmentally friendly products.